QUANTITATIVE AND QUALITATIVE CHANGES IN RED BONE MARROW MONOCYTE DIPHERONE AND MICROENVIRONMENTAL CELLS DURING LONG-TERM TRIPTORELIN ACETATE ADMINISTRATION IN THE EXPERIMENT - Martynenko, R.V.; Shepitko, V.I.; Pelypenko, L.B.; Boruta, N.V.; Martynenko, V.B.; Vilhova, O.V.; Stetsuk, Y.V. (World of Medicine and Biology, 2023)
Prostate cancer is the most common cancer diagnosis among men, with more than 160,000 new cases each year in the United States. Huggins and Hodges demonstrated the therapeutic effect of testosterone deficiency in the gonads in the 1940s and thus confirmed the concept that prostate cancer is an androgen-dependent disease. Androgen deprivation therapy (ADT) is the main palliative treatment for men with locally advanced and metastatic prostate cancer, with the goal of reducing testosterone levels to the level obtained by surgical castration. The long-term chemical castration with triptorelin acetate leads to quantitative and qualitative changes in monocytic sprout cells at all levels of differentiation and proliferation with a complementary reaction of microenvironmental cells. The maximum quantitative changes in monocyte cells were observed at the 3rd month of the study, followed by a gradual recovery to the control group. Changes in the microenvironment cells: macrophages and reticular cells, were characterized by a stable reaction in the early stages of the study in the form of a decrease in the number and ratio of NSCs, with subsequent recovery of quantitative and qualitative changes to the level of the control group of animals. The adipocyte reacts at all stages of the study with a steady increase in quantitative and qualitative characteristics.
Keywords: red bone marrow; monocytopoiesis; microenvironmental cells; triptorelin